The critical state of corporate social responsibility in Europe - Tench, Ralph; Jones, Brian, 1963 January 22-; Sun, William, 1962- (Critical studies on corporate responsibility, governance and sustainability ;, 2018)
European approaches to Corporate Social Responsibility (CSR) are supposed to be largely different from those in other continents like America, Asia, and Africa. Yet, European approaches to CSR are not a single and static one, but vary across and within national states and shift over time. This edited volume aims at exploring the uniqueness and complexity of European CSR approaches, perspectives, and practices through a critical lens. It contributes to existing understanding of European CSR by addressing the frontier CSR issues in the current state at the EU, national and institutional levels. Specifically, the volume critically examines the macro-level CSR frameworks, policies, and trends and their impact on CSR practices at the micro-level, including the roles of EU and national governments in shaping the CSR landscape in similar and different ways. It also analyses how various stakeholder groups and business sectors and firms across major European countries perceive, interpret and approach CSR in a dynamic way. Contributors of this book are experts mainly from Western and Eastern European countries and thus provide rich experiences, fresh insights, and deep understanding of the critical state of CSR in Europe.